2022
DOI: 10.11113/mjfas.v18n4.2516
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Anatomical Studies on Glycosmis perakensis V.Naray (Rutaceae)

Abstract: There are a number of underexplored plant species from the family of Rutaceae despite their economic importance, including Glycosmis perakensis V.Naray. Therefore, the main purpose of this study is to enhance its taxonomic characterization and identification of this plant species by examining the morphology and anatomy of selected parts. The histological procedure for G. perakensis stems and leaves were optimized by increasing the incubation time for the fixation, clearing, and infiltration steps of the standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…G. pentaphylla has a compound leaf comprised of 5 to 9 foliates. The leaf has elliptic to lanceolate shapes, alternate, with entire and unlobed margin (Sundrarajoo et al 2022). The morphological variations were also reported among the species under the genus Glycosmis, in terms of number of lea ets, number of ovary within the locule and fruit shape (Yasir et al 2018).…”
Section: )mentioning
confidence: 99%
“…G. pentaphylla has a compound leaf comprised of 5 to 9 foliates. The leaf has elliptic to lanceolate shapes, alternate, with entire and unlobed margin (Sundrarajoo et al 2022). The morphological variations were also reported among the species under the genus Glycosmis, in terms of number of lea ets, number of ovary within the locule and fruit shape (Yasir et al 2018).…”
Section: )mentioning
confidence: 99%
“…The genus is geographically distributed primarily in the south and southeastern Asia, Taiwan and South China as well as northern Australia and New Guinea, the tropical rainforest of Asia, Africa, Americas [1][2][3]. The shrubs or small trees have pinnate or simple leaves with translucent punctate glands emitting an aromatic odour when crushed [4][5][6][7][8][9]. Among spieces in the genus, some plants have been used as traditional medicine to against many diseases [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Others pharmacological functions of plant in this genus are treatment of cough, stomach pain, fever, liver complaints, jaundice, eczema and diarrhea [16]. These benefits are due to the abundance of phytochemical compounds such as terpenoids, alkaloids, flavonoids, sterols, amides,coumarins, imides, carbazoles, acridone, quinoline and quinazolines, some of them have shown bioactivities such as antiviral, antitumour, anti-inflammatory, hepatoprotective, antioxidant, antibacterial, anticancer, mosquito repellent, larvicidal activity [7,[17][18][19][20], etc. Rahman et al [21] reported about G. pentaphylla (Retz.)…”
Section: Introductionmentioning
confidence: 99%